Investigating EFL Students Reading Preferences (Digital or Printed) - Larasati, Finza; Adawiyah, Dita; Gumartifa, Asti (Yayasan Corolla Education Centre, 2023)
Reading is crucial to the process of learning a language. Students can use digital technology to support reading activities in today's modern culture. As a result of students' need for information in the digital age, digital text is now virtually everywhere. This study investigated EFL students reading preferences (digital or printed). The participants of this study were 102 EFL students from private universities in South Sumatera. The data was collected through 20 items of questionnaire distributed through google form. Based on the result of the study, it could be concluded that first, most participants enjoy reading. They read for a variety of purposes, including to get the knowledge, to get information, to get the entertainment, and for other purposes. The second, the participants prefer reading digital texts. The practicality of the digital texts is the primary motivating factor why they chose it. They acknowledged that they do not need to hold thick texts or books while reading, they only need to bring their devices. Furthermore, they said one device can store and read multiple texts. They added that reading materials on digital devices are considerably more intriguing and enjoyable than those on printed. Third, the researchers noted that all readers—whether they preferred reading printed or digital texts—felt at comfortable with the reading equipment they had selected. . Finally, it is revealed from the data that most participants are more inspired to read when they use digital reading texts.